Three new species of Begonia (section Baryandra, Begoniaceae) from Samar Island, the Philippines - Rubite, Rosario Rivera; Justo, Celeena Aimeree De Guzman; Villaseñor, Patricka Coliflores; Angeles, Marjorie D. Delos; Tandang, Danilo N.; Lin, Che-Wei (Phytotaxa, 2021)
The geographic location, climatic, and soil conditions of Samar Island render a mosaic of varied habitats which harbor numerous endemic, rare, and endangered species of plants. The island province is one of the centers of plant endemism in the Philippines. Included in this rich biodiversity of flora are members of genus Begonia of the family Begoniaceae. In 2018, researchers of the University of the Philippines found in the island three unknown Begonia species. With rhizomatous habits, persistent stipules, protandrous inflorescences, four-tepaled flowers, three winged capsules and bifid placenta, the three species are clearly members of Begonia section Baryandra. Studies of literature, herbarium specimens, and living plants support the recognition of the three new species: Begonia sohoton, Begonia tarangban and Begonia burabod.